Detection and serotyping of plum pox virus (PPV) isolates by monoclonal antibodies - Myrta A.; Boscia D.; Gavriel I. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
This surveys was carried out in Albania, Cyprus, Egypt, Greece, Italy, Lebanon, Malta and Turkey. No PPV was found in Lebanon and Malta, confirming previous reports. Detailed antigenic analyses among 170 PPV isolates from apricot, peach and plum originating from six Mediterranean countries, proved that they belong respectively to isolates M (139), D (20), EA (7) and (4) a mixture of strains (M+D). PPV-M was detected in Albania, Cyprus, Greece, Italy, and Turkey; PPV-D in Albania and Italy, and the strain mixture in two orchards in Albania. Several PPV-infected apricots from two Egyptian localities were recognised only by the MAb specific to El Amar serotype. This is the first report of a large-scale serotyping of PPV isolates in several Mediterranean countries.